Distributed Leadership Agency and Work Outcomes: Validation of the Italian DLA and Its Relations With Commitment, Trust, and Satisfaction - Barattucci, Massimiliano; Lo Presti, Alessandro; Bufalino, Giambattista; Jønsson, Thomas; Teresi, Manuel; Pagliaro, Stefano (Frontiers in Psychology, 2020)
Forms of collective leadership, such as Distributed Leadership, have become increasingly important. The need for measurement of the variables involved in the delegation processes, represents a new challenge for organizations that want to ensure high-level working. The present research aimed to validate the Italian version of the Distributed Leadership Agency (DLA) and verify its applicability in different contexts. The study involved all the employees of an Italian public Hospital, which were selected to complete a survey on organizational perceptions. The sample comprised 704 employees (doctors, nurses, clerks, staff workers, healthcare assistants, consultants, management). Multiple Confirmatory Factor Analyses (Maximum Likelihood) have been computed to explore the factorial structure of the DLA, along with associations with other work outcomes. Results clarified that the Italian DLA respects the tri-factorial structure of the construct, suggested by Yukl (2002), with good fit indexes and reliability; moreover, in line with the literature, DLA was strongly related to satisfaction, commitment, and trust. Results contribute to underline the robustness of the construct of distributed leadership agency in different cultural sectors, and provide a useful tool to be adopted in the Italian context.